1983
DOI: 10.1111/j.1365-2621.1983.tb14827.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of High‐Protein Low‐Cost Nigerian Foods

Abstract: Nigerian foods, akara, chii-chin, and puff-puff, were supplemented with full-fat cottonseed, defatted cottonseed, peanut, sesame or soybean flours. The foods were evaluated using a nine-point Hedonic scale by African and non-African panels. Foods were evaluated for appearance, texture, absence of greasiness, palatability and overall acceptability. The African panel rated all food products for all characteristics significantly (P=O.OOl) higher than the non-African panel. Protein quality evaluations indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…The protein content (15.5-25.6%) of the cookie formulations prepared in this study were higher than the protein levels (6-12%) reported for conventional wheat flour cookies 31,32 and other oilseed-supplemented wheat flour-based snack foods in Nigeria. 33 All the fluted pumpkin concentrate-supplemented cookies were considered to be nutritious since the consumption of about 100 g of each product formulation would provide more than half of the daily requirement for protein (25-30 g day −1 ) recommended by FAO/WHO 34 for children aged between 5 and 19 years. Recent recommendations of protein contents in cookies used in food aid programmes are 15.1-20.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The protein content (15.5-25.6%) of the cookie formulations prepared in this study were higher than the protein levels (6-12%) reported for conventional wheat flour cookies 31,32 and other oilseed-supplemented wheat flour-based snack foods in Nigeria. 33 All the fluted pumpkin concentrate-supplemented cookies were considered to be nutritious since the consumption of about 100 g of each product formulation would provide more than half of the daily requirement for protein (25-30 g day −1 ) recommended by FAO/WHO 34 for children aged between 5 and 19 years. Recent recommendations of protein contents in cookies used in food aid programmes are 15.1-20.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Akara is prepared in the home and by street vendors in the marketplace as a breakfast or snack food. Relatively unknown to the American palate, it has been indicated as the most common cowpea-based food product in Africa (Reber et al, 1983). Previous studies show this product can be prepared with equipment readily available in developed countries and has potential for home and institutional use.…”
mentioning
confidence: 99%
“…These crude protein values were comparable to the crude protein values of 19.3-20.9% reported for akara by other researchers 2,9 but were higher than the protein levels reported for some commonly consumed local snack or breakfast foods in Nigeria, such as agidi, a fermented maize meal (8.0%), bambara groundnut akara (15.4%), and chin-chin and puff-puff with protein levels ranging from 9.8 to 14.0%. 2,8,21 This suggests that these new cowpea varieties (IT81D-699 and TV x 3236) may be useful for the preparation of akara and other cowpeabased foods as protein sources for inclusion in the diet of malnourished Africans. Akara prepared from the blackeye variety had the highest ether extract content of 22.5%, compared with the ether extract contents ranging from 16.3 to 18.8% obtained for the other cowpea varieties.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 In Nigeria, akara is produced by street and market vendors, as well as in the home, using a local cowpea variety, the blackeye. 2,10,14 Studies on the production of akara using these newly developed cowpea lines have not been done. The aim of this study, therefore, was to evaluate the proximate composition, nutritional properties and acceptability of akara prepared using these new cowpea lines and to compare the results obtained with those for akara prepared from the local blackeye cowpea variety.…”
Section: Introductionmentioning
confidence: 99%